2009
DOI: 10.1536/ihj.50.571
|View full text |Cite
|
Sign up to set email alerts
|

Low HDL Levels as the Most Common Metabolic Syndrome Risk Factor in Heart Failure

Abstract: Metabolic syndrome (MetS) includes some parameters which are associated with cardiovascular events and risk of developing heart failure (HF). The aim of the present study was to explore the prevalence of metabolic syndrome and individual MetS parameters among heart failure patients. Stable HF patients who had an ejection fraction (EF) < or = 35% were included. They were evaluated for MetS and parameters according to the Adult Treatment Panel III (ATP III) of the National Cholesterol Education Program (NCEP). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
1
12
1
1
Order By: Relevance
“…298 Lastly, a small Turkish study of HFrEF reported a prevalence of 51%. 299 These studies uniformly found a higher prevalence of the metabolic syndrome in women than in men. Hispanics had the highest prevalence of the metabolic syndrome (78.8%) followed by whites (69.5%) and blacks (60.9%).…”
Section: Role Of the Metabolic Syndrome In Patients With Established Hfmentioning
confidence: 98%
“…298 Lastly, a small Turkish study of HFrEF reported a prevalence of 51%. 299 These studies uniformly found a higher prevalence of the metabolic syndrome in women than in men. Hispanics had the highest prevalence of the metabolic syndrome (78.8%) followed by whites (69.5%) and blacks (60.9%).…”
Section: Role Of the Metabolic Syndrome In Patients With Established Hfmentioning
confidence: 98%
“…187 In contrast, a low prevalence of hypertriglyceridemia was reported in MetS patients with advanced heart failure owing in part to hepatic congestion and cachexia. 188 …”
Section: Prevalence Of Elevated Triglyceride In Metsmentioning
confidence: 99%
“…A low level of HDL-cholesterol (HDL-C) is a well-defined risk factor for the development of cardiovascular diseases 6 and overall survival in general, 7 even when LDL-C levels are optimally controlled. 8,9 More recently, evidence has accumulated that a low HDL-C level also is an independent risk factor for the development of diabetes.…”
Section: Low High-density Lipoprotein Levels As a Risk Factor For Diamentioning
confidence: 99%